Struktur Komunitas MakrozoobentoS di Perairan Pandansari Kecamatan Sayung Kabupaten Demak - Zulfiandi, Zulfiandi; Zainuri, Muhammad; Hartati, Retno (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Pandansari estuary waters is an area which flood by high tide or known as â€œrobâ€and became a shallow water area. Macrozoobenthos is used as one of the biological component in monitoring of water quality. The purpose of this study was to determine the macrozoobenthos community structure in Pandansari waters, District of Sayung, Demak. There were 4 stations earned 48 genera consist of 7 class, including in the 6 phyla of Molluscs (35 species), Polychaeta (17 species), Crustaceans (5 species), Sipuncula (1 species), nematodes (1 species) and Nemertina (1 species). Macrozoobenthos abundance ranged from 1.910-21.442 ind/m3, with a diversity index of 0.45-2.67, which indicated that the carrying capacity of Pandansari waters to support macrozoobenthos live is low to moderate. The evenness index ranged from 0.23-0.97 are in the category of small to high which indicated the proportion is not the same type of macrozoobenthos, and dominance index of 0.08-0.82, which indicated there was species dominating macrozoobenthos in the waters of Pandansari, district of Sayung, Demak.